2015
DOI: 10.1016/j.juro.2015.01.083
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative AST/ALT (De Ritis) Ratio Represents a Poor Prognostic Factor in a Cohort of Patients with Nonmetastatic Renal Cell Carcinoma

Abstract: In our study cohort with nonmetastatic renal cell carcinoma the preoperatively assessed AST/ALT ratio represented an independent prognostic factor. This ratio might further improve the predictive accuracy of well established prognosis scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
143
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 28 publications
2
143
1
1
Order By: Relevance
“…The optimal cut-off value for the continuous AAR was calculated by applying a receiver operating curve analysis to test all possible cut-offs that would discriminate between CLI and non-CLI as previously described. [12] …”
Section: Methodsmentioning
confidence: 99%
“…The optimal cut-off value for the continuous AAR was calculated by applying a receiver operating curve analysis to test all possible cut-offs that would discriminate between CLI and non-CLI as previously described. [12] …”
Section: Methodsmentioning
confidence: 99%
“…AAR was subsequently used to predict the presence of progressive fibrosis in chronic hepatic B patients and poor survival in chronic viral hepatitis C 24. In recent years, AAR has been shown to be a useful predictor for nonhepatic diseases and a prognostic biomarker in certain types of malignant tumor 11,1416,24–27. For example, in a large European cohort of nonmetastatic renal cell carcinoma patients, Bezan et al identified preoperative AAR as a predictor of a poor clinical outcome 11.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, AAR has been shown to be a useful predictor for nonhepatic diseases and a prognostic biomarker in certain types of malignant tumor 11,1416,24–27. For example, in a large European cohort of nonmetastatic renal cell carcinoma patients, Bezan et al identified preoperative AAR as a predictor of a poor clinical outcome 11. Nishikawa et al discovered that preoperative AAR was significantly correlated with a fourfold increase in an unfavorable prognosis in patients with upper urinary tract urothelial carcinoma 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of chronic renal failure has been rising, due to increasing prevalence of conditions such as diabetes or viral hepatitis, which can be associated with renal damage. In addition, AST and ALT levels, which provide the De Ritis ratio [24], have been previously reported as significant prognostic biomarkers in several malignancies including kidney diseases [25]. The mechanism underlying the relationship of AST and RCC is related to the vital role of AST in glycolysis by relocation of NADH into the mitochondria through the malate-aspartate shuttle pathway, in which clear cell RCC with VHL loss was known to induce the expression of hypoxia factors known to be connected to extensively increased glycolysis in the mitochondria, which is well-known as the Warburg effect [26, 27].…”
Section: Discussionmentioning
confidence: 99%